Economic Pressure and Self-Efficacy as Independent Predictors of Academic Grades and Career Indecision for Southern European Middle School Students: A Confirming Study - Antonio Citarella; Juan José Maldonado Briegas; Ana Isabel Sánchez Iglesias; Florencio Vicente Castro (Frontiers in Education, 2020)
Using data from the same sample of previous Citarella's (2018) study, this paper aims to confirm the independent role playing by economic pressure due to Great Recession and self-efficacy in determining educational outcomes for middle school students in Southern Italy context. Additionally, the role of mastery goal orientation was tested for this study. Three basic moderation model were developed using Amos (21) and Process (13.4) for SPSS software to test (1) the moderated effect of self-efficacy in the relationship between economic pressure and outcomes; (2) the interaction between self-efficacy and mastery goal orientation in predicting outcomes; (3) the moderated effect played by self-efficacy plus mastery goal orientation in the relationship between economic pressure and outcomes. Results showed that self-efficacy does not moderated the predicting effect of economic pressure on grades and career indecision. Mastery goal orientation positively interact with self-efficacy in predicting outcomes but the moderated effect of the two added integrated constructs was not significantly. Hence, the independent role of economic factors and agency was confirmed by this study.